A Rare Case of Bilateral Maxillary Paramolars between 1st and 2nd Molars - Shetty, Y Naresh (Journal of Orofacial Research, 2012)
Paramolars are supernumerary teeth usually found buccally or palatally near the molars. Very few articles are found in the literature about bilateral maxillary paramolars. Most of the cases, the paramolars are situated between the second and third molars, while in very few cases, as in our case it was found between first and second molars. The present article presents a case of bilateral maxillary paramolars in a 26-year-old male patient and its management.